Flexor and Extensor Ankle Afferents Broadly Innervate Locomotor Spinal Shox2 Neurons and Induce Similar Effects in Neonatal Mice - Li, Erik Z.; Garcia-Ramirez, D. Leonardo; Dougherty, Kimberly J. (Frontiers in Cellular Neuroscience, 2019)
Central pattern generators (CPGs) in the thoracolumbar spinal cord generate the basic hindlimb locomotor pattern. The locomotor CPG integrates descending commands and sensory information from the periphery to activate, modulate and halt the rhythmic program. General CPG function and response to sensory perturbations are well described in cat and rat models. In mouse, roles for many genetically-identified spinal interneurons have been inferred from locomotor alterations following population deletion or modulation. However, the organization of afferent input to specific genetically identified populations of spinal CPG interneurons in mouse remains comparatively less resolved. Here, we focused on a population of CPG neurons marked by the transcription factor Shox2. To directly test integration of afferent signaling by Shox2 neurons, sensory afferents were stimulated during patch clamp recordings of Shox2 neurons in isolated spinal cord preparations from neonatal mice. Shox2 neurons broadly displayed afferent-evoked currents at multiple segmental levels, particularly from caudal dorsal roots innervating distal hindlimb joints. As dorsal root stimulation may activate both flexor- and extensor-related afferents, preparations preserving peripheral nerves were used to provide more specific activation of ankle afferents. We found that both flexor- and extensor-related afferent stimulation were likely to evoke similar currents in a given Shox2 neuron, as assessed by response polarity, latency, duration and amplitude. It has been proposed that Shox2 neurons can be divided into neurons which contribute to rhythm generation and neurons that are premotor by the absence and presence of the V2a marker Chx10, respectively. Response to afferent stimulation did not differ based on Chx10 expression. Although currents evoked in response to flexor and extensor afferent activation did not follow expected functional antagonism, they were consistent with the observation that stimulation of flexor- and extensor-related afferents both reset the phase of ongoing fictive locomotion to flexion. Together, the data suggest that Shox2 neurons are interposed in multiple sensory pathways and low threshold proprioceptive input reinforces sensory perturbation of ongoing locomotion by similarly activating or inhibiting both the rhythm and patterning layers of the CPG.